PENGARUH PENAMBAHAN RAGI ROTI DAN WAKTU FERMENTASI TERHADAP KARAKTERISTIK CUKA DARI NIRA LONTAR (Borassus flabellifer Linn) - Antonius Solo; G.P. Ganda Putra; I Putu Suparthana (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2019)
Indonesia's natural resources are rich in biodiversity which is a very prospective potential to bedeveloped. One of them is palm tree. The main result of palm tree was sap. Palm sap can be processedinto sugar or vinegar. This study aims to know the effect of addition of bread yeast and fermentationtime on the characteristics of vinegar, determine the best treatment of adding bread yeast and fermentation time to produce vinegar from sap palm (Borassus flabellifer Linn), and to know the stabilityof vinegar products for storage temperature. The experimental design used was factorial CompletelyRandomized Design with 2 factors, namely the addition of bread yeast (0%, 1%, 2%, 3%, 4% and 5%)and fermentation time (0, 10, 15, 20, 25 and 30 days). The data obtained were analyzed by ANOVA andif the treatment had a significant effect it was followed by the Duncan test. The results showed that (1)the treatment of adding bread yeast had an effect on acetate levels, alcohol content, total soluble solidsand pH; but does not affect total sugar; fermentation time affects the level of acetic acid, total sugar,alcohol content, total soluble solids and pH; while the interaction between treatments has an effect ontotal soluble solids and pH, but does not affect acetic acid levels, total sugar and alcohol content onvinegar from fermented of palm sap, (2) treatment of addition of 5% bread yeast with 30 daysfermentation time was the best treatment for producing vinegar, with characteristics of acetic acid levelof 2.72% v / v, total sugar 0.03%, alcohol content 0.68% and total soluble solids 2.60 °Brix; (3) thestability of vinegar products produced at various storage temperatures an affects the levels of aceticacid and total soluble solids.